Three complete mitochondrial genomes of freshwater fishes in the genus Abbottina (Cypriniformes: Gobionidae). Issue 2 (3rd July 2019) - Chen, Yun; Fu, Cuizhang
Abstract: Abbottina binhi has been misidentified as Abbottina rivularis in China for a long time. In this study, we determined three mitochondrial genomes of A. rivularis and A. binhi such that these data should contribute to molecular identifications of the two species. The size of new mitochondrial genomes was 16, 609 or 16, 599 bp with A + T bias of 55.7–56.5% in the base compositions. Our reconstructed phylogeny showed that A. rivularis and A. binhi formed a sister taxon relationship, and they together were a monophyletic group.